Mechanical behavior of M-Wire and conventional NiTi wire used to manufacture rotary endodontic instruments - Pereira, Erika S.J.; Gomes, Renata O.; Leroy, Agnès M.F.; Singh, Rupinderpal; Peters, Ove A.; Bahia, Maria G.A.; Buono, Vicente T.L. (Dental materials, 2013)
Comparison of physical and mechanical properties of one conventional and a new NiTi wire, which had received an additional thermomechanical treatment. Specimens of both conventional (NiTi) and the new type of wire, called M-Wire (MW), were subjected to tensile and three-point bending tests, Vickers microhardness measurements, and to rotating-bending fatigue tests at a strain-controlled level of 6%. Fracture surfaces were observed by scanning electron microscopy and the non-deformed microstructures by transmission electron microscopy. The thermomechanical treatment applied to produce the M-Wire apparently increased the tensile strength and Vickers microhardness of the material, but its apparent Young modulus was smaller than that of conventionally treated NiTi. The three-point bending tests showed a higher flexibility for MW which also exhibited a significantly higher number of cycles to failure. M-Wire presented mechanical properties that can render endodontic instruments more flexible and fatigue resistant than those made with conventionally processed NiTi wires.